Effects of Human Activities from the Indo-Gangetic Plain on the Air Quality in the Foothills of the Himalayas - Kishore, Nand; Koranga, Bipin Singh; Srivastava, Atul Kumar (Journal of Graphic Era University, 2025)
The relationship between surfaces that measure climatic parameters and the mass concentration of various air pollutants across the Indo-Gangetic Plain (IGP) and Himalayan foothills is investigated using three separate stations. In an industrial area of Delhi, a residential area of Shimla, and a residential area of Hisar, the simultaneous measurement of mass concentrations of air pollutants such as NO2, SO2, RSPM, and SPM, as well as the impact of surface meteorological parameters on their distributions, are investigated for the study period of January 2005 to December 2012. The seasonal variations in air pollutants were also examined. Additionally, a regression analysis between the daily mass concentration of air pollutants and metrological parameters has been carried out. The correlation coefficients between climatic factors and air pollutants were found to be positive with the exception of the correlations between wind direction and SO2 and visibility and NO2. Additionally, the time series of AOD and ASMF, two MODIS-derived daily and monthly mean columnar aerosol parameters, are examined over Delhi, Hisar, and Shimla from 2005 to 2012. The maximum and minimum AOD values for Delhi, Hisar, and Shimla, respectively, are 2.3 and 0.08, 3.5 and 0.09, and 2.6 and 0.06. However, at all three locations, ASMF fluctuated between 0 and 1. The highest values of AOD were observed in the months of June and August, with a pattern of increasing values from January to June and a pattern of decreasing values from August to December. While an increasing pattern was seen during the post-monsoon and winter months, ASMF was found to diminish from February up to April or May. A back-trajectory analysis of the air mass is used to examine the effects of the observed increased air pollution from the IGP over the Himalayan city of Shimla. The trajectories (23%) passing over the IGB in a southeasterly direction were seen to have an impact on Shimla.